2009
DOI: 10.1111/j.1532-849x.2009.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Load at Fracture of Turkom‐Cera to Procera AllCeram and In‐Ceram All‐Ceramic Restorations

Abstract: Because Turkom-Cera demonstrated equal to or higher loads at fracture than currently accepted all-ceramic materials, it would seem to be acceptable for fabrication of anterior and posterior ceramic crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The results of this study for Turkom-Cera and In-Ceram copings were in agreement with those obtained in a previous study (AL-Makramani et al, 2009), which found that TurkomCera had a significantly higher load at fracture than Procera AllCeram. Furthermore, the results of this study for In-Ceram and Procera AllCeram copings were in agreement with those obtained in previous studies (Webber et al, 2003;Neiva et al, 1998;Harrington et al, 2003;AL-Makramani et al, 2009), which found no significant differences in load at fracture between Procera AllCeram and In-Ceram copings that were resin cemented.…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The results of this study for Turkom-Cera and In-Ceram copings were in agreement with those obtained in a previous study (AL-Makramani et al, 2009), which found that TurkomCera had a significantly higher load at fracture than Procera AllCeram. Furthermore, the results of this study for In-Ceram and Procera AllCeram copings were in agreement with those obtained in previous studies (Webber et al, 2003;Neiva et al, 1998;Harrington et al, 2003;AL-Makramani et al, 2009), which found no significant differences in load at fracture between Procera AllCeram and In-Ceram copings that were resin cemented.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…The results of this study for Turkom-Cera and In-Ceram copings were in agreement with those obtained in a previous study (AL-Makramani et al, 2009), which found that TurkomCera had a significantly higher load at fracture than Procera AllCeram. Furthermore, the results of this study for In-Ceram and Procera AllCeram copings were in agreement with those obtained in previous studies (Webber et al, 2003;Neiva et al, 1998;Harrington et al, 2003;AL-Makramani et al, 2009), which found no significant differences in load at fracture between Procera AllCeram and In-Ceram copings that were resin cemented. An in vitro study (AL-Makramani et al, 2009), which evaluated the fracture resistance of Turkom-Cera, In-Ceram and Procera AllCeram copings cemented on a metal master die using resin luting cement, shows that the load necessary to fracture the Turkom-Cera, InCeram and Procera AllCeram copings in the current study was less than that reported in that study.…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…using a ball or a bar to apply load 5) or the type of the underlying abutment 46) . Consequently there is a variation in results between different investigations 47) . Further variables with this testing result from the design and reproducibility of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Resin bonding of ceramic restorations to the supporting tooth structure increases the fracture resistance of the restored tooth and the restoration itself [9,17,18]. Many studies have evaluated the fracture strength of allceramic crowns [4,[19][20][21][22][23][24][25][26][27][28][29][30][31] using metal [4,21,23,25], brass [19,26], acrylic resin [20], epoxy resin [24,27], and dentin [22] as supporting die materials. Increasing the elastic modulus of the supporting die material has been suggested as a means to increase the fracture resistance of all-ceramic posterior crowns [11].…”
Section: Introductionmentioning
confidence: 99%